HALTRAV: Design of a High-Performance and Area-Efficient Latch With Triple-Node-Upset Recovery and Algorithm-Based Verifications - Guo, Xing; Zhang, Jiajia; Meng, Xu; Li, Zhenmin; Wen, Xiaoqing; Girard, Patrick; Liang, Bin; Yan, Aibin (IEEE transactions on computer-aided design of integrated circuits and systems, 2025)
With the rapid advancement of semiconductor technologies, latches become increasingly sensitive to soft errors, especially triple node upsets (TNUs), in harsh radiation environments. In this article, we first propose a high-performance and area-efficient latch, namely, HALTRAV, featuring complete TNU-recovery. The storage portion of HALTRAV consists of 28 interlocked source-drain cross-coupled inverters (SCIs) for complete TNU-recovery with area efficiency and low delay. To mitigate the issue that node-upset-recovery verifications for existing latches highly relies on electronic design automation tools, we further propose an algorithm-based verification method that can automatically verify the node-upset-recovery of latches, which greatly simplifies the reliability-verification flow. Simulation results demonstrate the TNU-recovery of HALTRAV and also show that HALTRAV achieves 40.38%, 8.17%, and 31.89% reduction in delay, area, and delay-power-area product (DPAP) on average, respectively; however; it is at the cost of power as compared to typical latches that are TNU-recoverable. Comparison results also demonstrate the moderate sensitivity of HALTRAV to the impacts of the process, voltage, and temperature (PVT) variations.